2014
DOI: 10.1071/wf12202
|View full text |Cite
|
Sign up to set email alerts
|

Representation and evaluation of wildfire propagation simulations

Abstract: Abstract. This paper provides a formal mathematical representation of a wildfire simulation, reviews the most common scoring methods using this formalism, and proposes new methods that are explicitly designed to evaluate a forest fire simulation from ignition to extinction. These scoring or agreement methods are tested with synthetic cases in order to expose strengths and weaknesses, and with more complex fire simulations using real observations. An implementation of the methods is provided as well as an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…Our evaluation relies on scoring methods that were analysed (and, for two of them, proposed) in Filippi et al (2013). We denote S(t) as the burned surfaces at time t in the simulation.…”
Section: Comparison Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Our evaluation relies on scoring methods that were analysed (and, for two of them, proposed) in Filippi et al (2013). We denote S(t) as the burned surfaces at time t in the simulation.…”
Section: Comparison Scoresmentioning
confidence: 99%
“…The first step in evaluating model performance is to be able to evaluate single simulation results against observations. Such scoring methods have been the subject of several studies, initiated by Fujioka (2002) and recently compiled and extended in Filippi et al (2013). Basically, it is clear from all these studies that a single value cannot be representative of a model performance, as it only gives limited insights on all aspects of performance, while the analysis of a human eye provides a better understanding of what was good and what went wrong.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have sought to validate fire spread simulation systems by comparing simulated fire spread against historical fire data, for example the studies of Finney (Finney 2000), Fujioka (Fujioka 2002), Arca et al (Arca et al 2007), and Fillipi et al (Filippi et al 2014). In common with previous validation exercises, this study found that that the ability to perform validation was limited by the reliability of available data, with fireground weather presenting the largest obstacle.…”
Section: Discussionmentioning
confidence: 82%
“…We test it by assimilating airborne infrared images captured from two large-scale experiments conducted in South Australia and assess the forecast reliability by means of Jaccard (Jaccard 1901;Filippi et al 2014c) and Sørensen (Sørensen 1948;Perry et al 1999) similarity indices, finding great agreement in the available short-term forecast.…”
Section: Introductionmentioning
confidence: 99%